Dyspnea in amyotrophic lateral sclerosis: The Dyspnea-ALS-Scale (DALS-15) essentially contributes to the diagnosis of respiratory impairment. (July 2019) - Vogt, S.; Schreiber, S.; Kollewe, K.; Körner, S.; Heinze, H.-J.; Dengler, R.; Petri, S.; Vielhaber, S.
Abstract: Background: Dyspnea is a cardinal but often underestimated symptom in amyotrophic lateral sclerosis (ALS). The newly developed Dyspnea-ALS-Scale (DALS-15) is highly relevant for therapeutic decisions because dyspnea is a separate criterion to consider noninvasive ventilation (NIV) in ALS. In comparison to the limited effects of neuroprotective compounds, NIV has the greatest impact on survival and improves quality of life. Objective: To investigate whether dyspnea corresponds to parameters of respiratory status mainly used in clinical neurological practice. We also investigated if the DALS-15 could help identify patients for consideration of NIV in whom neither spirometry nor blood gas parameters indicate the need for NIV (forced vital capacity (FVC) < 50% or probable <75%, pCO2 ≥45 mmHg). Methods: Seventy ALS patients with dyspnea according to the DALS-15 obtained blood gas analysis and spirometry (FVC in sitting and supine positions). The supine decline in FVC was calculated. Results: There was no linear relationship between dyspnea and spirometry as well as blood gases. 83% of our patients had an upright FVC still greater than 50% and no daytime hypercapnia. Conclusions: Our study clearly shows that dyspnea can occur independently of objective indicators of respiratory impairment like spirometry or blood gases. Hence, the DALS-15 covers another aspect of respiratory impairment than these tests and refers to the subjective component of respiratory impairment. It detects dyspnea in a considerable proportion of patients in whom NIV should thus be considered although their spirometric and blood gas results do not point towards NIV. The DALS-15 therefore may help to improve the stratification of patients with respiratory impairment for more efficient symptom management and timely coordination of care. Highlights: Dyspnea can occur independently of objective indicators of respiratory impairment. The DALS-15 detects dyspnea as a subjective component of respiratory impairment. The DALS-15 identifies patients with dyspnea in whom NIV should thus be considered. In 83% of our patients with dyspnea neither FVC nor pCO2 indicated the need for NIV. The DALS-15 therefore provides essential information for the initiation of NIV.